Faktor Penentu Imunisasi Dasar Lengkap pada Anak di Wilayah Kerja Puskesams di Kota Palembang - Sartika, Veira Delli; Mastina, Mastina; Rahmawati, Eka (Poltekkes Kemenkes Palembang, 2023)
WHO mention about 1.5 million children die each year because diseases that can be prevented by immunization. Immunization is one of the health interventions that has proven to be the cheapest, because it can prevent and reduce the incidence number of morbidity, disability, and death due to PD3I (Ministry of Health RI, 2020). Infants aged 0-11 months must receive complete basic immunization consisting of 1 dose of Hepatitis B, 1 dose of BCG, 3 doses of DPT-HB-HiB, 4 doses of polio drops (OPV), 1 dose of injectable polio (IPV) and 1 dose of measles rubella. In 2020, complete basic immunization in the city of palembang is 81.9% and this means that it has not reached the 2023 national target of 100%. The immunization coverage of Boom Baru Health Center reached 96.4%. The purpose of this study was to find out what factors are related to the coverage of complete basic immunization in children at the Boom Baru Health Center in Palembang City. This study used quantitative methods with a cross sectional approach. Data collectiom used a questionnaire and analyzed univariately to describe distribution and proportion, and bivariate used Chi Square. This study found that there was no relationship between mother’s last education with complete basic immunization coverage (p = 0.143), and there was a relationship between mother’s knowledge (p = 0.000), Trust (p = 0.000), family support (p = 0.000). This study suggest for health workers provide counseling and increase the motivation of mothers regarding the importance of immunization and do monitor the completeness of their immunization, while mothers who have babies should take the time to immunize their chidren. Bibliography : 2010-2023 Keywords : Basic Immunizations, Education, Knowledge, Trust, Family Support